EFEKTIVITAS UPTD. BALAI BENIH IKAN PALUH PAKEH DINAS PERIKANAN DAN KELAUTAN KABUPATEN LANGKAT - , HERRY DAVID SAGALA, Dr. Ely Susanto, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Since the law of local autonomy applied in 2001, it makes the regional cities have their own right in making the decision to arrange and develop their own regions. Therefore the regional government must work hard in discovering the potensials that their regions has to fulfill the needs of their citizens and the government and the minister of fisheries and marine affairs is one of it. Aquaculture in one of the subfactor which has great potential to be developed. Therefore to develop this area, the Ministry of Marine Affairs and Fisheries designs a program to increase the production up to 353 % by the year 2015. To reach that goal, Ministry of Marine Affairs and Fisheries release the policy to build the facilities to develop the the fisheries and marine in the regions, one of it is building hatchery/ fish seed (UPTD Balai Benih Ikan). District of Langkat located in the North Sumatra province is one of the regions which has that potential. Based on the data from the fisheries and marine Agency of Langkat District, that Langkat District has freshwater aquaculture potential about 1000Ha, only 112 Ha that is used with 597 RTP. Regarding the decision of the Ministry of Marine Affairs and Fisheries, For implementation of parts of Fisheries and Marine Agency Assignments and by analyzing the potential that they have, then the Fisheries and Marine Agency of Langkat District think that it is very essential to build the UPTD. Balai Benih Ikan as the media to produce the excellent in quality and quantities fish seed. According to the data, it is shown that UPTD Balai Benih Ikan cant reach to produce the fish seed as it potential owned yearly then it called not effective. Therefore, this thesis is design to find out the problems and its solutions to the problems. From the observation results it is found that the uneffectiveness of the decentralitation, leadership, motivation, the human rescources ability and technology make the UPTD BBI Paluh Pakeh Fisheries and Marine Agency of Langkat District doesnât work properly therefore it needs repairing.